Intertekstualitas dalam Novel “Hati Suhita” Karya Khilma Anis - Eliya, Ixsir; Lida, Ulfah Mey; Nurpadillah, Veni; Rachman, Anita Kurnia; Nuthihar, Rahmad (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This study describes the intertextual relationship between the characters and plot of the novel